Implementation of Knowledge Management System in the Indonesian History Community - Harahap, Nurul Haifa; Setiawati, Nur Fitri Rosa; Akoso, Muhammad Daffa Raihan; Siregar, Johannes Hamonangan (Jurnal Teknik Indonesia, 2025)
Komunitas Historia Indonesia (KHI) is one of the leading historical communities in Indonesia that plays an important role in preserving and disseminating historical knowledge to the public. In the digital era, the challenges in maintaining the continuity of knowledge and collaboration between community members are increasing. Therefore, the implementation of the Knowledge Management System (KMS) is relevant to manage, store, and disseminate historical knowledge effectively. This article discusses how the implementation of KMS can improve the effectiveness of KHI community activities, as well as the obstacles and opportunities faced in the process. The method used is a literature study of KMS literature and documentation of community activities. Keywords : Knowledge Management System, Historical Community, Knowledge Preservation, Komunitas Historia Indonesia.